Non-invasive instrumental analytical methods in modern pharmaceutical technology - Joanna Ronowicz; Natalia Piekuś-Słomka (Polish Pharmaceutical Society, 2020)
The purpose of this work is the evaluation of the state of knowledge in the scope of the possibility of using of non-invasive analytical methods in the implementation of Process Analytical Technology strategy, which is currently recommended by worldwide registration agencies. The drug product quality should be based on risk analysis. Effective risk management is possible through the implementation of innovative process analysis technology (PAT strategy). The pursuit of an efficient production control system makes non-invasive techniques particularly important. These techniques provide the ability to monitor each stage of the manufacturing process, and thus identify defects during the manufacture of drug dosage forms. The infrared spectroscopy, Raman spectroscopy and pulsed terahertz spectroscopy are gaining in importance. Research articles describe the application of Raman imaging, scanning electron microscopy or atomic force microscopy in the evaluation of pharmaceutical formulations. These methods facilitate making accurate technological decisions that guarantee the desired drug product quality. The need to adapt to current regulations and recommendations of regulatory authorities in the field of process control systems forces the search for new analytical methods allowing for the collection of process data in real-time. In recent years, innovative instrumental analytical methods such as optical coherence tomography, X-ray microtomography and microwave resonance have gained popularity. In comparison to the traditional approach to the drug product quality assurance, the PAT strategy assumes a holistic approach by integrating the manufacturing process with simultaneous control of all production stages. It seems extremely important to automate the manufacturing process control so that it is carried out without interrupting production as part of so-called continuous process verification. Due to a better process understanding and accurate identification of sources of variation in the manufacturing process, the implementation of PAT strategy seems to be necessary to obtain the desired drug product quality in a repeatable manner. The principle of continuous process and product quality improvement focuses on reducing the manufacturing process variability by continuous process monitoring using non-invasive and non-destructive instrumental analytical methods.